2014
DOI: 10.1038/srep06015
|View full text |Cite
|
Sign up to set email alerts
|

Controlling resistant bacteria with a novel class of β-lactamase inhibitor peptides: from rational design to in vivo analyses

Abstract: Peptide rational design was used here to guide the creation of two novel short β-lactamase inhibitors, here named dBLIP-1 and -2, with length of five amino acid residues. Molecular modeling associated with peptide synthesis improved bactericidal efficacy in addition to amoxicillin, ampicillin and cefotaxime. Docked structures were consistent with calorimetric analyses against bacterial β-lactamases. These two compounds were further tested in mice. Whereas commercial antibiotics alone failed to cure mice infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
(43 reference statements)
0
8
0
1
Order By: Relevance
“…This represents at least a 16-fold decrease in the concentration of antibiotic required to eradicate such biofilms [39]. It would be interesting to determine whether peptides such as DJK-6 act as β-lactamase inhibitors, as this has been shown to be an activity of certain peptides [41]. …”
Section: Synthetic Antibiofilm Peptidesmentioning
confidence: 99%
“…This represents at least a 16-fold decrease in the concentration of antibiotic required to eradicate such biofilms [39]. It would be interesting to determine whether peptides such as DJK-6 act as β-lactamase inhibitors, as this has been shown to be an activity of certain peptides [41]. …”
Section: Synthetic Antibiofilm Peptidesmentioning
confidence: 99%
“…Strains used included clinical isolates Escherichia coli KPC-positive ID N°.181244635 , Escherichia coli multiresistant ID N°.210112335 and carbapenemase-producing Klebsiella pneumoniae 1825971 (KPC971), as well as reference strains Bacillus subtilis ATCC 6633, Enterococcus faecalis ATCC 12953, Staphylococcus aureus ATCC 29213, Methicillin-Resistant Staphylococcus aureus ATCC 33591, Streptococcus pyogenes ATCC 19615, Escherichia coli ATCC 8739, Klebsiella pneumoniae ATCC 13885, Proteus mirabilis ATCC 25933, Pseudomonas aeruginosa ATCC 15442 and Salmonella enterica ATCC 14028. Bacteria were plated on brain heart infusion (BHI) agar (Himedia, India) from a frozen stock.…”
Section: Methodsmentioning
confidence: 99%
“…Based on preliminary experiments to determine an effective challenge bacterial inoculum [ E. coli ATCC 8739 and E. coli KPC-positive ID N°.1812446 or S. aureus ATCC 29213 and S. aureus (MRSA) ATCC 33591] that resulted in consistent systemic infection without rapidly killing the mice (data not shown), mid-log-phase bacteria were diluted to ~2 × 10 7 CFU/mouse in PBS for Gram-negative bacteria and ~2 × 10 9 CFU/mouse in PBS for Gram-positive bacteria121335. Mice were challenged by i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] Research studies in the last decade have shown that the most promising approach to overcoming resistance to β-lactam antibiotics requires high throughput screening of new non β-lactam scaffolds, those demonstrating inhibitory activity against a large family of β-lactamases, in addition to the improvement of established antibiotics. [11][12][13][14][15] This research aimed to discover new β-lactamase inhibitors by employing a combination of molecular docking and biochemical kinetics assays. We first focused on discovery of novel 3D-pharmacophores and fragments from the family of diphenyl, aromatic ketone, hydroxy-phenyl derivatives and stilbene, all previously described by others to exhibit antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%